The Effect of Social Norm-based Intervention with Observable Behaviour on Physical Activity among Adolescents: A Randomized Controlled Trial - Jia Jia LEE; Nivedita Vikas NADKARNI; Irene TEO; Semra OZDEMIR (BMC, 2020)
Abstract Background The rising prevalence of childhood obesity in developing and developed countries poses a major public health challenge to policy makers and an effective strategy to promote physical activity among adolescents is warranted. This study aimed to evaluate the effectiveness of providing descriptive norms messages with personal identification in promoting physical activity among adolescents by measuring step counts via a randomized controlled trial (NCT03081013). Methods A total of 311 participants aged 13-16 were randomized into two study arms (Onymous and Anonymous Arms). Each arm consisted of 13 groups of 12 participants. During the trial, participants received weekly short message service (SMS) about their past week's physical activity performance. Participants in the Anonymous Arm received information about step counts of group members ranked from highest to lowest. Participants in the Onymous Arm received the same information with the group members' full names. Participants' quality of life, depression, physical activity social support, self-efficacy and enjoyment before and after the intervention were also evaluated. This study adheres to the CONSORT guidelines. Results The number of steps was not higher when descriptive norm message was onymous compared to when it was anonymous. Scores in quality of life, depression, social support, self-efficacy, and enjoyment of physical activity were not significantly different between both arms (p > 0.05). Conclusions Our findings indicated that the effect of providing descriptive norms messages containing personal identification on physical activity promotion was not evident in the main analysis. Future studies may consider using a more relevant reference group to use social norms as a tool to increase physical activity among adolescents. Trial registration ClinicalTrials.gov - NCT03081013 . Registered 15 Mar 2017-Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03081013